2022
DOI: 10.1002/eap.2649
|View full text |Cite
|
Sign up to set email alerts
|

Application of modern coexistence theory to rare plant restoration provides early indication of restoration trajectories

Abstract: Restoration ecology commonly seeks to re-establish species of interest in degraded habitats. Despite a rich understanding of how succession influences re-establishment, there are several outstanding questions that remain unaddressed: are short-term abundances sufficient to determine long-term reestablishment success, and what factors contribute to unpredictable restorations outcomes? In other words, when restoration fails, is it because the restored habitat is substandard, because of strong competition with in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 47 publications
0
20
0
Order By: Relevance
“…Importantly, our results also demonstrated that the rate of community turnover can remain high as communities approach and reach equilibrium states (Figure 5). As such, we advocate that future work on succession and community assembly incorporate fluctuation dependent coexistence and stochastic theory, as communities at their dynamical equilibrium can be highly variable (Hallett et al, 2019;Shoemaker et al, 2020;Aoyama et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, our results also demonstrated that the rate of community turnover can remain high as communities approach and reach equilibrium states (Figure 5). As such, we advocate that future work on succession and community assembly incorporate fluctuation dependent coexistence and stochastic theory, as communities at their dynamical equilibrium can be highly variable (Hallett et al, 2019;Shoemaker et al, 2020;Aoyama et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…However, without continual removal, recruitment from exotic populations adjacent to the restored pools allowed for eventual recolonization of the site. Previous studies have shown that restored native populations can subsequently decline and even go extinct due to low growth rates that are negatively affected by interannual environmental variability and competition by invasive species (Aoyama et al 2022). Indeed, other long‐term monitoring studies in other ecosystems, such as grasslands and forests, have also shown that restored plant communities never reach the species diversity of natural reference ecosystems (McClain et al 2011; Lesage et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…In such settings, after the implementation phase ends, isolated restored sites may become reinvaded quickly by undesirable species from the surrounding landscape. Even if there are native individuals present, environmental conditions (e.g., climate change, competition) may prevent population growth and even result in local extirpation (Aoyama et al 2022). For example, restored wetlands that established an average of 28 native species within the implementation phase subsequently experienced a decline in richness to 12 native species 6 years later (Gutrich et al 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, our results also demonstrated that the rate of community turnover can remain high as communities approach and reach equilibrium states (Figure 5). As such, we advocate that future work on succession and community assembly incorporate fluctuation dependent coexistence and stochastic theory, as communities at their dynamical equilibrium can be highly variable (Aoyama et al, 2022;Hallett et al, 2019;Shoemaker et al, 2020).…”
Section: Conc Lusionmentioning
confidence: 99%